Analysis of the Sputum Culture Spectrum of Children with Respiratory Tract Infection in Wuxi Between 2014 and 2021 - Jia HL; Gao J; Ren F; Ma Y (Infection and Drug Resistance, 2023)
Hong-Liang Jia,1 Jian Gao,2 Feng Ren,2 Yaping Ma1 1Department of Pediatrics, Affiliated Hospital of Jiangnan University, Wuxi, 214122, People’s Republic of China; 2Department of Clinical Laboratory, Affiliated Hospital of Jiangnan University, Wuxi, 214122, People’s Republic of ChinaCorrespondence: Yaping Ma, Department of Pediatrics, Affiliated Hospital of Jiangnan University, No. 1000 of Hefeng Road, Binhu District, Wuxi, 214122, People’s Republic of China, Tel +86 510-68089896, Email mayp987@163.comObjective: We retrospectively analysed related clinical data to determine the influencing factors to better prevent and treat children’s respiratory tract infection.Methods: The study participants were children with respiratory tract infection who had sputum cultured in our hospital between 2014 and 2021. Sputum samples were extracted using negative suction pressure and sent to the hospital microbiological laboratory for testing. The testing results were analysed.Results: A total of 4610 sputum samples were collected, and 508 positive samples were detected. The positive rate of pathogenic bacteria was 11.02%. Escherichia coli infection was more common in male patients (11.11%), whereas Haemophilus influenzae infection was more common in female patients (17.54%); the infection rates of these 2 bacteria are increasing annually. There were 304 (59.84%) strains of gram-negative bacteria, 172 (33.86%) strains of gram-positive bacteria and 32 (6.3%) strains of fungi. In children between 0 and 3 years old, the proportions of gram-negative bacteria were significantly higher than those of gram-positive bacteria in 2016– 2017, 2018– 2019 and 2020– 2021 (p